2010
DOI: 10.1177/1091581810386124
|View full text |Cite
|
Sign up to set email alerts
|

Amended Safety Assessment of Dodecylbenzenesulfonate, Decylbenzenesulfonate, and Tridecylbenzenesulfonate Salts as Used in Cosmetics

Abstract: Sodium dodecylbenzenesulfonate is one of a group of salts of alkylbenzene sulfonates used in cosmetics as surfactant-cleansing agents. Sodium dodecylbenzenesulfonate is soluble in water and partially soluble in alcohol, with dermal absorption dependent on pH. Dodecylbenzenesulfonate salts are not toxic in single-dose oral and dermal animal tests, and no systemic toxicities were observed in repeat-dose dermal animal studies. In dermal animal studies, no evidence of reproductive or developmental toxicity was rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…This is also borne out by the continued growth of cells on the scaffolds, which do not appear to be adversely affected by the presence of DBSA or indeed the potential for its presence in the surrounding media. DBSA is a surfactant used in some cosmetics, therefore, cytotoxic effects may generally be those of a detergent which can be tolerated by cells at low concentrations . The stability of the conductivity of DBSA‐containing scaffolds speak to the excellent compositional properties of the scaffolds and their future application for longer‐term monitoring of cell cultures.…”
Section: Assessing Electrical Properties Of Pedot:pss Scaffolds Beformentioning
confidence: 99%
“…This is also borne out by the continued growth of cells on the scaffolds, which do not appear to be adversely affected by the presence of DBSA or indeed the potential for its presence in the surrounding media. DBSA is a surfactant used in some cosmetics, therefore, cytotoxic effects may generally be those of a detergent which can be tolerated by cells at low concentrations . The stability of the conductivity of DBSA‐containing scaffolds speak to the excellent compositional properties of the scaffolds and their future application for longer‐term monitoring of cell cultures.…”
Section: Assessing Electrical Properties Of Pedot:pss Scaffolds Beformentioning
confidence: 99%
“…However, benzalkonium chloride belongs to the cationic surfactants group of quaternary ammonium compounds that are found to be highly toxic to different aquatic organisms as well as being capable of inducing genotoxic effects in mammalian and plant cells [43]. Similarly, sodium dodecylbenzene sulfonate was reported to cause severe irritancy in rabbit skin at a concentration of 15% [44]. With the appearance and prevalence of multi-drug resistant microorganisms in the hospital settings along with the toxicity issues related to widely employed commercial disinfectants, the exploration of alternative antimicrobial agents from other sources, especially from plants is in high demand.…”
Section: Discussionmentioning
confidence: 99%
“…coli (BL21) were transformed with pT3-5-LO plasmid, and recombinant 5-LO protein was expressed and partially purified as described [50]. In brief, cells were lysed in 50 mM triethanolamine/HCl pH 8.0, 5 mM EDTA, soybean trypsin inhibitor (60 µg/mL), 1 mM phenyl-methanesulphonyl fluoride, and lysozyme (1 mg/mL), homogenized by sonication (3 × 15 s), and centrifuged at 40,000× g for 20 min at 4 • C. The 40,000× g supernatant was applied to an ATP-agarose column to partially purify 5-LO as described [44]. Aliquots of semi-purified 5-LO were immediately diluted with ice-cold PBS containing 1 mM EDTA, and 1 mM ATP was added.…”
Section: -Lo Activity In Cell-free Assaysmentioning
confidence: 99%
“…A single occluded dose of ∼20 mg/cm 2 (1,500 mg/kg) [ 14 C]diethanolamine was applied to a 19.5 cm 2 area on the back of rats for 6 hours, and the treated site of half of the animals was rinsed after the occlusive wrapping was removed. 26 In the animals that were not rinsed, 80% of the dose was found in the wrappings and 3.6% found in the skin.…”
Section: Toxicokineticsmentioning
confidence: 99%
“…In 2009, the Expert Panel reviewed the safety of DEA-dodecylbenzenesulfonate, an ingredient included in this rereview. 2 It was concluded that DEA-dodecylbenzenesulfonate is safe as used when formulated to be nonirritating.…”
Section: Introductionmentioning
confidence: 99%